“E você é de onde?” Crenças e atitudes linguísticas acerca da palatalização das oclusivas alveolares /t/ e /d/ diante de /i/ em Fortaleza-CE - Freitas, Maylle Lima (2024)
This study investigates linguistic beliefs and attitudes regarding the palatalization of alveolar stops [t] and [d] before /i/, resulting in affricates [tʃ] and [dʒ] in the speech community of Fortaleza-CE. Ceará is conducive to studying this phenomenon, as palatalization is the norm in the capital, Fortaleza, while alveolar stops prevail in the interior of the state, especially in the Cariri region. The theoretical framework draws on Language Variation and Change theory (Weinreich; Labov; Herzog, 2006 [1968]; Labov, 2008 [1972]; Labov, 1994; Labov, 2001), social meaning of variation (Eckert, 2008; Eckert, 2012; Campbell-Kibler, 2009; Oushiro, 2015, 2021), dialectal contact, second dialect acquisition, and linguistic accommodation (Giles; Coupland, N.; Coupland, J., 1991; Garret, 2010; Sigel, 2010; Britain, 2010). A Linguistic Beliefs and Attitudes Test was developed using equivalent stimuli, a technique referred to in this study as Pseudo-Matched Guise, produced by 2 volunteers (1 male and 1 female) residing in Fortaleza-CE with a history of living in Cariri, sometimes producing the occlusive variant, and sometimes the palatal one. The test analyzed the participants' social profiles, discrete variables (list of status and dynamism characteristics), ordinal variables on Likert scales (levels of accent, northeastern identity, and "sung speech"), and (meta)linguistic evaluation of the variants. 255 responses were obtained from the questionnaire, with most participants being from Fortaleza, Ceará (62.35%) and Cariri, Ceará (16.86%), female (63.92%), with higher education (82.75%), and aged up to 29 years (50.98%). Regarding migrants, most moved to Fortaleza for study purposes (38.54%) and had been living in the city for 0 to 10 years (46.88%). Data analysis was performed using R programming to generate tables, graphs, ordinal regression models with mixed effects, and minimum distance trees. It was concluded that the occlusive variant is highly salient and stigmatized in the capital city of Ceará, being the subject of metalinguistic comments and evaluative social attitudes in dialectal contact situations. The variant is also associated with social characteristics of solidarity and the attribution of northeastern identity, accent, and "sung speech". This study also highlighted the interaction between gender and age in the perception of northeastern identity, especially regarding occlusives, as these attributed higher scores on the northeastern identity scale than younger men. For the subgroup of migrants, it was noted that migration reasons indicating the participant's autonomy in the migration process (work and study) disadvantaged the attribution of northeastern identity to the variant. The occlusive variant was less perceived as an accent by male participants, natives of the Cariri region, and migration time in years for these migrants. Migration reason was again relevant, as those who moved for family reasons attributed more accent to their variant of origin. For the perception of "sung speech" style for the occlusive variant, education and age were significant and supportive of this evaluation, while men disadvantaged this evaluation. For Cariri migrants, there was a greater attribution of this characteristic to participants who migrated for study reasons and have lived in Fortaleza for more than 2/3 of their lives, in this group, the longer migration time in years disadvantaged this evaluation, suggesting a chronological influence on the evaluation. Despite the associated stigma, the occlusive variant was considered "beautiful" both in metalinguistic evaluation and in participants' reports, thus demonstrating the complexity associated with the dimensions of solidarity and status in linguistic variation and the concept of stigmatization of prominent linguistic variants, with a pattern of lower-status variants being well-rated in terms of solidarity. Finally, it is pointed out that the occlusive variant is the target of linguistic prejudice, and migrants from the interior of Ceará, with an emphasis on the Cariri region, face evaluative pressures to linguistically accommodate to the variety of Fortaleza-CE and be better understood and integrated into the new speech community.